2011
DOI: 10.1063/1.3602326
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of aluminum clusters with water

Abstract: The atomistic mechanism of rapid hydrogen production from water by an aluminum cluster is investigated by ab initio molecular dynamics simulations on a parallel computer. A low activation-barrier mechanism of hydrogen production is found, in which a pair of Lewis acid and base sites on the cluster surface plays a crucial role. Hydrogen production is assisted by rapid proton transport in water via a chain of hydrogen-bond switching events similar to the Grotthuss mechanism, where hydroxide ions are converted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 51 publications
5
43
0
Order By: Relevance
“…[40][41][42][43][44][45][46] It includes also a number of theoretical studies on the structural aspects of Al clusters, [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] and about their interaction [65][66][67][68][69][70][71][72] and reaction [73][74][75][76][77][78][79] with simple molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43][44][45][46] It includes also a number of theoretical studies on the structural aspects of Al clusters, [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] and about their interaction [65][66][67][68][69][70][71][72] and reaction [73][74][75][76][77][78][79] with simple molecules.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The observed fast reaction rates and calculated low reaction energy barriers are explained by the same reaction mechanisms as in our previous study. 22,23 In addition, we find that the formation and breaking up of branching H-bonds, which connect the H-bond chain with the solvation shell, are crucial to facilitate proton transfer. This explains why the energy barrier varies strongly upon the rearrangement of surrounding water molecules, generally resulting in extremely low values (< 0.1 eV) in the presence of branching H-bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous quantum molecular dynamics (MD) study investigated H 2 production of the magic-number Al n (n = 12, 17) in liquid water. 22,23 It is found that proton transfer along a chain of hydrogen bonds (H-bonds) between water molecules, i.e. Grotthuss mechanism, [24][25][26][27][28] plays an important role not only in splitting water into surface hydrogen and hydroxyl groups, but also in recombining hydrogen atoms into hydrogen molecules.…”
Section: Introductionmentioning
confidence: 99%
“…12 Other ligand-stabilized metal clusters are known in addition to the aluminum compounds; thiolprotected gold clusters, for example, have received significant recent attention due to their application in nanomedicine and biochemistry. 8,9,20 Beyond the basic interest in ligand-protected cluster stability, there is also recent interest in the use of small aluminum clusters as catalysts for producing hydrogen from water 21,22 or as high energy-density fuels. 23 Aluminum powder is frequently used as a fuel component due to its high enthalpy of combustion.…”
Section: Introductionmentioning
confidence: 99%